Improving HCV Screening in Addiction Care Centers with Plasma Separation Cards - Fernando Velásquez Orozco; David Tabernero; María Gabriela Barbaglia; Lara Treviño; Begoña Trujillo; Andrés Marco; Miguel Ángel Carrillo; Gerard Ruiz Salinas; Francesc Xavier Majo Roca; Joan Colom Farran; María Buti; Tomas Pumarola-Sunyer; et al. (Pathogens)
Globally, 50 million people are infected with hepatitis C virus (HCV), many of whom are people who inject drugs. These individuals face healthcare barriers, necessitating innovative diagnostic tools. This study evaluated the impact of cobas plasma separation cards (PSCs) for dry plasma collection in Barcelona’s outpatient drug addiction centers (CAS). From February to December 2021, nine CASs were invited to implement PSC for HCV screening; three centers participated, allowing for the assessment of its impact on HCV detection. Of the 679 clients screened, 54 (8%) provided finger-prick blood samples via PSC due to their refusal or inability to undergo venipuncture. Overall, 100 (14.7%) clients tested positive for HCV antibodies, with 24 (24%) confirmed as HCV-RNA positive. Among venipuncture clients, 9.1% had positive antibodies, with 15.8% showing active infection. In contrast, 79.6% of PSC clients had positive antibodies and 34.9% had detectable HCV RNA, contributing to 62.5% of the active infections detected. The odds ratio was 26.3, indicating that refusal or inability to undergo venipuncture correlated with a significantly higher burden of active HCV infection. The findings highlight PSC as a valuable alternative for diagnosing HCV in people with substance use disorders, addressing accessibility barriers and improving linkage to care in high-risk populations.